Modern view on the treatment of diabetic macular edema - A.V. Shelankova; M.V. Budzinskaya; I.V. Andreeva (Офтальмохирургия)
Purpose. To evaluate modern methods of the treatment of diabetic macular edema (DME). Material and methods. When writing a literature review, data was searched on the PubMed and Scopus platforms for the period up to 2021 inclusive. The search was carried out using the following keywords: diabetic macular edema, Ozurdex, dexamethasone implant, anti-VEGF, meta-analysis. A total of 33 articles were selected that are relevant to the topic of this literature review. Results. DME is one of the most common causes of vision loss in the world, especially in patients of working age. However, the choice of the treatment for DME is still controversial among vitreoretinal specialists. The pathophysiological process of DME development includes several mechanisms associated with chronic hyperglycemia. It has been proven that the level of vascular endothelial growth factor (VEGF) in the eye is not only elevated in DME, but is also proportional to the severity of edema. The use of anti-VEGF drugs for intravitreal administration for the treatment of DME has improved the prognosis of visual functions. The efficacy and safety of anti-VEGF drugs has been confirmed in many clinical studies. However, more and more data appear in the literature on the fairly common resistance to anti-VEGF therapy. Based on the foregoing, the experts concluded that it is necessary to revise the DME treatment strategy and conduct additional studies in order to identify other approaches in therapy to improve visual acuity. In patients with diabetes mellitus, high concentrations of pro-inflammatory cytokines were found. Corticosteroids have an anti-inflammatory effect, including reducing the permeability of the vascular walls, thereby giving an angiostatic effect in the treatment of DME. Thus, the dexamethasone implant may be a better alternative in the treatment of DME. Conclusion. Based on these studies, it can be concluded that the use of Ozurdex in the treatment of DME can be used both as the main treatment for DME and as an alternative treatment for patients who «poorly respond» to multiple injections of anti-VEGF drugs or in cases of resistance. Dexamethasone has the highest clinical efficacy among all corticosteroids used in ophthalmic practice, the drug demonstrates its multifaceted effects due to its influence on various links in the pathogenesis of DME. Dexamethasone implant reduces the concentration of both inflammatory cytokines in the eye and VEGF.